2017
DOI: 10.17582/journal.pjz/2017.49.6.2113.2121
|View full text |Cite
|
Sign up to set email alerts
|

Ixodid Ticks (Arachnida: Acari) Prevalence Associated with Risk Factors in the Bovine Host in District Quetta, Baluchistan

Abstract: Authors' Contribution NR and AK conceived and designed the study. AG, WMA, SS, MAM and MS collected data. NR, AK and WMA analyzed the data. AK wrote the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Despite the above, few studies have been conducted and published on people's knowledge, attitude, and practices regarding tick and TBDs, with even fewer from Pakistan, where TBDs are causing devastating economic losses [50][51][52][53][54][55][56]. With this in mind, the current study was designed to evaluate livestock owner's knowledge, attitude, and practices towards ticks in Punjab, Pakistan, to assess the awareness about ticks and TBDs, zoonotic concerns, and need for a One Health approach towards tick control in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above, few studies have been conducted and published on people's knowledge, attitude, and practices regarding tick and TBDs, with even fewer from Pakistan, where TBDs are causing devastating economic losses [50][51][52][53][54][55][56]. With this in mind, the current study was designed to evaluate livestock owner's knowledge, attitude, and practices towards ticks in Punjab, Pakistan, to assess the awareness about ticks and TBDs, zoonotic concerns, and need for a One Health approach towards tick control in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed the delayed tick activity with an increase in altitude and decrease in temperature (Daniel et al, 2003). During past decades due to global warming, a higher tick infestation is reported at higher altitudes further elaborating the relationship between tick prevalence and temperature (Gray et al, 2009;Gilbert, 2010;Rafiq et al, 2017). Endemicity of the tick infestation might be due to the geographical changes and/or climatic conditions of the different study areas making acari able to maintain their survival where these were not prevalent earlier (Wikel, 2018).…”
Section: Ecological Impact On the Ticks And Tick-borne Diseasesmentioning
confidence: 72%
“…Of all the examined cattle, 77.91% were found to be infested with ticks ( 55 ). In Baluchistan province (Quetta city) prevalence was 65.96% in the cattle ( 56 ). Of the total observed farmed cattle in a study from 2017, 89.9% were infested with ticks in the semiarid and arid agro-ecological zones from Punjab ( 6 ).…”
Section: Resultsmentioning
confidence: 99%